Tourism planning and destination marketing - Camilleri, Mark Anthony (Emerald Publishing Limited, 2024)
Authored by more than 20 leading academics and providing in-depth coverage of a wide array of economic, social, technological and environmental realities in tourism planning and development, this volume is the latest in the field of travel and tourism. Contemporary topics are explored in-depth, including destination branding through cultural experiences; the planning and organisation of events; the promotion of the hospitality product, eco-tourism and sustainable practices; and the use of innovative tourism technologies such as digital media, augmented and virtual reality. The course content of this publication prepares undergraduate students and aspiring managers with a thorough exposure of the latest industry and research developments. Covering both theory and practice, it introduces its readers to contemporary tourism issues in a concise yet accessible way. This allows prospective tourism practitioners to critically analyse future situations and to make appropriate decisions in their workplace environments. Key terms are defined and clearly explained in the latter part of every chapter. This provides readers with a convenient source for learning and reviewing the tourism vocabulary that is required for effective communication on the job. Each chapter also contains a succinct summary that outlines its content in a condensed form, so as the readers could review and retain key information. Experiential exercises and case studies are provided to illustrate real situations that are meant to help aspiring managers in their future employment. Course conveners may use these cases as the basis of class discussions. In addition, web resources provide further information sources.